Accustomed to Obedience? Classical Ionia and the Aegean World, 480-294 BCE - Nudell, Joshua P. (University of Michigan Press, 2023)
Many histories of Ancient Greece center their stories on Athens, but what would that history look like if they didn't? There is another way to tell this story, one that situates Greek history in terms of the relationships between smaller Greek cities and in contact with the wider Mediterranean. In this book, author Joshua P. Nudell offers a new history of the period from the Persian wars to wars that followed the death of Alexander the Great, from the perspective of Ionia. While recent scholarship has increasingly treated Greece through the lenses of regional, polis, and local interaction, there has not yet been a dedicated study of Classical Ionia. This book fills this clear gap in the literature while offering Ionia as a prism through which to better understand Classical Greece. This book offers a clear and accessible narrative of the period between the Persian Wars and the wars of the early Hellenistic period, two nominal liberations of the region. The volume complements existing histories of Classical Greece. Close inspection reveals that the Ionians were active partners in the imperial endeavor, even as imperial competition constrained local decision-making and exacerbated local and regional tensions. At the same time, the book offers interventions on critical issues related to Ionia such as the Athenian conquest of Samos, rhetoric about the freedom of the Greeks, the relationship between Ionian temple construction and economic activity, the status of the Panionion, Ionian poleis and their relationship with local communities beyond the circle of the dodecapolis, and the importance of historical memory to our understanding of ancient Greece. The result is a picture of an Aegean world that is more complex and less beholden narratives that give primacy to the imperial actors at the expense of local developments.